CORRELATION OF C-REACTIVE PROTEIN (CRP), AND INTERLEUKIN-6 (IL-6) WITH HEPCIDIN LEVELS IN PATIENTS WITH ANEMIA OF CHRONIC DISEASE (ACD) - Giri Prebawa, I Putu Arya; Suega, Ketut (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Anemia of chronic disease (ACD) or anemia of chronic inflammation is the most common cause of anemia in hospitalized patients. Recent studies revealed that interleukin-6 (IL-6), C-reactive protein (CRP), and Hepcidin play a key role in ACD pathogenesis. This study is an observational study with a crossectional approach that aims to see the relationship between levels of inflammatory marker such as CRP and IL-6 with Hepcidin on the incidence of ACD at Prof Ngoerah Hospital Denpasar. This study involved 92 samples. Descriptive analysis will be presented in the form of tables and narratives for all data obtained in this study. Bivariate analysis was carried out using the Spearman correlation. The mean CRP level of the patients in this study was 89.1 ± 80.1 mg/L which could be categorized as high. The mean Il-6 level of the patients in this study was 91,8±88,4 pg/mL which could be categorized as high and the Hepcidin level in this study was 64.4 ± 49.9 ng/dL. This study shows that inflammation plays a role in increasing levels of Hepcidin which plays a role in the pathogenesis of ACD. This can be seen from the significant positive correlation between Hepcidin levels and IL-6 levels (P=0,00), although there is no correlation between Hepcidin and CRP. Inflammation plays a role in increasing levels of Hepsidin which plays a role in the pathogenesis of ACD.